2011
DOI: 10.1002/ejoc.201101427
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Annulation Reactions of Bisenolates Prepared Through Dearomatization Reactions of Aromatic and Heteroaromatic Diesters

Abstract: A one-pot, enantioselective strategy for the dearomatizationannulation of aromatic diesters to give a range of highly functionalized polycyclic molecules with excellent enantioselectivity is presented. This methodology is based on the reaction of bisenolates, prepared by treating aromatic diesters with trialkyltin lithium reagents, which involves a stanna-Brook rearrangement, with 1,ω-dihaloalkanes and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Sardina, Paleo, and co-workers (2012) started from diisopropyl benzofuran-2,3-dicarboxylates that were treated under stanna-Brook conditions to give the corresponding bisenolate and these were alkylated with various 1,-dihaloalkanes to give the corresponding tricyclic compounds in good yields. 145 A biocatalytic strategy was also reported in 2019 by Zhang, Fasan, and co-workers for the highly diastereo-and enantioselective construction of stereochemically rich DHBs. Cyclopropanation of benzofurans with engineered myoglobins gave cyclopropane-fused benzofurans in high T. Laurita et al…”
Section: Scheme 61 Asymmetric Iridium-catalyzed Hydrogenation Of Alkymentioning
confidence: 90%
“…Sardina, Paleo, and co-workers (2012) started from diisopropyl benzofuran-2,3-dicarboxylates that were treated under stanna-Brook conditions to give the corresponding bisenolate and these were alkylated with various 1,-dihaloalkanes to give the corresponding tricyclic compounds in good yields. 145 A biocatalytic strategy was also reported in 2019 by Zhang, Fasan, and co-workers for the highly diastereo-and enantioselective construction of stereochemically rich DHBs. Cyclopropanation of benzofurans with engineered myoglobins gave cyclopropane-fused benzofurans in high T. Laurita et al…”
Section: Scheme 61 Asymmetric Iridium-catalyzed Hydrogenation Of Alkymentioning
confidence: 90%
“…In 2012, the research group of Paleo reported (Scheme 1A), [6a] dearomatization of benzofuran‐2,3‐diesters 1 through a 2,3‐dialkylation process employing 1,n‐diiodides (n=3–5) 2 as electrophiles in the presence of Me 3 SnLi for the synthesis of annulated products 3 . Later they have also developed an enantioselective formal [4+2] cycloaddition reaction (Scheme 1B) employing the chiral diesters 4 (prepared from monoacid‐monoester 5 ), and 1,4‐dimesylate 6 as the reactant.…”
Section: Dearomatization Of Benzofuransmentioning
confidence: 99%
“…By using this last type of methodology, we have studied the synthesis of fused bicyclic compounds from aromatic diesters in a one-pot dearomatization-bisalkylation reaction. This transformation can be realized in two ways: (a) through a nucleophilic-stanna-Brook rearrangement pathway, by using of (trialkylstannyl)­lithium reagents, , or (b) by reductive means using alkaline metals. , In both cases, a bis -enolate intermediate is formed, which is trapped with a suitable bis -electrophile. For heteroaromatic diesters (pyridine, furane, or benzofurane) better results are obtained with trialkyltinlithium reagents, but for all-carbon aromatic diesters both routes lead to similar yields of the desired bicyclic products, and the later is preferable as hazardous tin reagents are avoided.…”
Section: Introductionmentioning
confidence: 99%